Just like Millie - Castillo, Lauren (Candlewick Press, 2024)
"When a young girl and her mother move to an apartment in a new city, the girl feels fine on her own. She would rather play by herself than meet new kids at the park or have a playdate with the other children in her building. And when her mom takes her to story time at the bookstore, she breaks down in tears. But things start to change when she meets Millie, a rescue dog who is not too big, not too small. On their daily walks, Millie isn't afraid to meet new people seems to like friends. When she sees another shy girl at the dog park, will the girl find the courage to be just like Millie and make new friends?"--Jacket flap.